The effect of crocin on total sleep-deprivation induced amnesia in male Wistar rats - Lootibashiyan, Malihe; Nasehi, Mohammad; Khalifeh, Solmaz; Zarrindast, Mohammad-Reza (Archives of Advances in Biosciences, 2018)
Introduction: In recent years, Crocin has been used for its pharmacological functions, such as memory and learning enhancement. The aim of the present study was to assess the effect of Crocin on total sleep deprivation (TSD)-induced amnesia in male Wistar rats. Materials and Methods: The water box apparatus was used to induce sleep deprivation followed by Y- maze task as an index of learning and memory (the percentage of time in the novel arm during the retention phase was reported as an index of memory performances). The rats were divided into 12 groups, 8 rats in each group, including four control groups, four sham groups, and four TSD groups. Each group received saline and Crocin at doses of 1, 5 or 15 mg/kg twice a day. Results: The findings revealed that TSD for 24 h impaired memory function. In addition, the intra-peritoneal injection of Crocin at all doses (1, 5 and 15 mg/kg) did not change the percentage of time spent in the novel arm of Y-maze in sham of TSD, whereas it abolished the responses induced by the TSD groups. Conclusion: The findings showed a close interaction between the Crocin and SD. Based on the findings, Crocin seems to possess a modulatory effect on SD-induced amnesia.